Fat graft augmentation rhinoplasty compared to costal cartilage graft in saddle nose panfacial fractures - Dini Widiarni Widodo; Satria Dipo Putra Asmoro; Raden Ayu Anatriera (PERHATI-KL, 2021)
ABSTRACTBackground: Panfacial fracture can cause nasal function and esthetics alterations, one of which is saddle nose deformity. Post-traumatic saddle nose could be treated with augmentation rhinoplasty to correct the nasal structure and function. It can use autologous material such as fat graft and cartilage graft. Purpose: To report the effect of fat graft augmentation rhinoplasty compared to costal cartilage graft on patients’ satisfaction of saddle nose panfacial fracture cases. Case report: Reporting two cases of panfacial fracture with saddle nose. The first case, a 22-years-old female with multiple facial fractures underwent plate and screw fixation and nasal fracture close reduction followed by augmentation rhinoplasty using fat graft. The second case was a 23-years-old male diagnosed as blow-out fracture treated with internal fixation and costal cartilage augmentation rhinoplasty. Clinical question: Does fat graft augmentation rhinoplasty result in a better satisfaction level than costal cartilage graft in panfacial fracture with saddle nose cases. Review method: Evidence-based literature searching was performed through Pubmed, Scopus and Proquest databases to evaluate the effect of rhinoplasty augmentation using fat graft compared to costal cartilage on patient satisfaction level. Result: One study showed patient’s high satisfaction level after fat graft augmentation procedure. Another study showed that satisfaction rates were also high in cartilage graft augmentation patients. Conclusion: The advantages of using fat graft augmentation are the more natural esthetic outcome, easy to perform and low morbidity. Rhinoplasty Outcome Evaluation (ROE) questionnaire could be used to evaluate the outcome of augmentation rhinoplasty with high sensitivity and specificity.Keywords: saddle nose, panfacial fracture, fat graft augmentation, costal cartilage graft, ROEABSTRAKLatar belakang: Fraktur panfasial dapat mengakibatkan perubahan struktur wajah disertai kelainan fungsi dan estetika hidung, salah satunya deformitas saddle nose. Saddle nose pasca trauma wajah dapat ditatalaksana dengan rinoplasti augmentasi untuk memperbaiki struktur dan fungsi hidung. Rinoplasti augmentasi dapat menggunakan material tandur autologous misalnya tandur lemak dan kartilago. Tujuan: Melaporkan hasil augmentasi tandur lemak dibandingkan tandur kartilago iga terhadap tingkat kepuasan pasien kasus saddle nose fraktur panfasial. Laporan kasus: Dua kasus fraktur panfasial disertai saddle nose. Kasus pertama, perempuan 22 tahun dengan fraktur wajah multipel, dilakukan fiksasi internal menggunakan plate and screw dan reduksi tertutup fraktur nasal, dilanjutkan rinoplasti augmentasi tandur lemak untuk memperbaiki saddle nose. Kasus kedua, laki-laki 23 tahun dengan fraktur blow-out ditatalaksana dengan fiksasi internal dilanjutkan rinoplasti augmentasi tandur kartilago iga. Pertanyaan klinis: Apakah rinoplasti augmentasi tandur lemak menghasilkan tingkat kepuasaan pasien lebih baik dibandingkan tandur kartilago iga pada kasus saddle nose pada fraktur panfasial? Telaah literatur: Pencarian literatur mengenai pengaruh augmentasi tandur lemak dibanding tandur kartilago iga terhadap tingkat kepuasan pasien fraktur panfasial dalam database Pubmed, Scopus dan Proquest. Hasil: Satu artikel menunjukkan tingkat kepuasan pasien pasca rinoplasti augmentasi tandur lemak yang tinggi dengan tingkat morbiditas rendah. Artikel lain menunjukkan tingkat kepuasan yang juga tinggi pada pasien augmentasi tandur kartilago tanpa komplikasi mayor. Kesimpulan: Keuntungan penggunaan tandur lemak pada rinoplasti adalah terlihat lebih alami, lebih mudah dilakukan dengan morbiditas rendah, akan tetapi dengan tingkat resorpsi tinggi. Kuesioner Rhinoplasty Outcome Evaluation (ROE) dapat menjadi alat untuk menilai outcome dari rinoplasti augmentasi dengan sensitivitas dan spesifitas cukup tinggi.Kata kunci: saddle nose, fraktur panfasial, augmentasi tandur lemak, tandur kartilago iga, ROE